Gestión de las cuentas por cobrar y su incidencia en la liquidez de la empresa - Avila Anastacio, Nestor Michael (2019)
The company Imporparis, S.A. it has problems in its availability of cash to honor obligations with third parties, to which this research was conducted to determine the causesusing the analytical, historical and documentary method. The financial statements were analyzed, indicators were applied and workers from the administrative and accounting areas wereinterviewed to determine the cause of this illiquidity. Finding that the origin of the same, is basedon the long periods of collection of accounts receivable, product of a disorganization in credisales policies. Finally, several actions are recommended to mitigate this situation….